Կանանց կերպարային դրսևորումները հայ և եվրոպական գրականության մեջ (ԺԱ-ԺԴ դդ․) - Թամանյան, Նաիրա Իլյայի (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Women's images in European and Armenian literary cultures were formed mainly under the influence of biblical systems and express the realities, social, social and moral norms of the time. Unlike European literature, Armenian literature lacks chivalric novels, which was conditioned by other social and historical circumstances. Female characters can be conditionally grouped by archetypes (maiden, mother, faithful wife, wise woman, heroic woman, deceiver, sinner, victim, femme fatale), the characteristics of which can be combined in one manifestation of character.
Keywords: Հայ գրականություն; Եվրոպական գրականություն; Կանանց կերպարներ